188k views
2 votes
For a given input value b, the function g outputs a value a to satisfy the following equation. a-7=3(b+2)a−7=3(b+2)

Write a formula for g(b) in terms of b

2 Answers

1 vote

Answer: 3b +13

Explanation:

User TheNoobGuy
by
5.8k points
6 votes

Answer:

g(b) = 3b +13

Explanation:

Effectively, you want to solve for "a".

a-7 = 3(b+2)

a = 3b +6 + 7 . . . . . . eliminate parentheses, add 7

g(b) = 3b +13

User Yogesh Manware
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.